2014
DOI: 10.1002/cctc.201402261
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Activity of Plasmonic Photocatalysts

Abstract: Plasmonic photocatalysts, which have intensive light absorption and high charge‐separation efficiencies, are regarded as promising candidates to solve energy and environmental issues in the future. In this Review, we summarize recent developments in the synthesis, activity, and mechanism of plasmonic photocatalysts, with the aim of stimulating improvements in photocatalytic activities and promoting the development of photocatalysis. The materials systems, energy‐transfer mechanisms, and factors that influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
90
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 165 publications
0
90
1
1
Order By: Relevance
“…The intragap states present in black TiO 2 play a key role in promoting both DET and PRET mechanisms, as recently demonstrated by Naldoni et al [92]. Enhancement by SPR has been adopted in many application fields of photocatalysis [93], including mineralization of organic pollutants and H 2 generation. Priebe et al demonstrated how various parameters affect the performance of plasmonic Au/TiO 2 materials in H 2 production from aqueous MeOH solution under visible light [94].…”
Section: Increasing Activity Under Visible Light: Self-doping Vs Surfmentioning
confidence: 93%
“…The intragap states present in black TiO 2 play a key role in promoting both DET and PRET mechanisms, as recently demonstrated by Naldoni et al [92]. Enhancement by SPR has been adopted in many application fields of photocatalysis [93], including mineralization of organic pollutants and H 2 generation. Priebe et al demonstrated how various parameters affect the performance of plasmonic Au/TiO 2 materials in H 2 production from aqueous MeOH solution under visible light [94].…”
Section: Increasing Activity Under Visible Light: Self-doping Vs Surfmentioning
confidence: 93%
“…Possible alternatives might be Cu-and Al-based plasmonic photocatalysts. Also nonmetal-based plasmonic photocatalysts, as reviewed in [205], might set the path for low-cost materials as effective photocatalysts. It has to be pointed out that photocatalytic stability is considered one main challenge for efficient photocatalysts and is investigated by various research groups besides the targeted high enhancements in photocatalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…If the produced composite incorporates into an appropriate matrix like SBA15, much more active sites can be exposed originating from the decreased particle size and a large amount of pollutant molecules tend to gather around active sites as a result of the strengthened adsorption ability from support, further benefiting photocatalytic processes [19][20][21][22]. The deposition of noble metal nanoparticles on surface of semiconductors is another efficient manner to promote photocatalytic efficiency through the formation of schottky junction at the metalsemiconductor interfaces and the LSPR effect by metallic noble elements [23][24][25]. The former is able to induce the directional migration of electrons and hereby causes the separation of charge carriers [26,27].…”
Section: Introductionmentioning
confidence: 99%